(3eTGcd GdeQGLYI aj CShGb GdeGds - (3CMeO UdGM(B, (3YWjIs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2003)
(3ebOeI aj WHjYI GdGShGb GdeGdjI(B- (3eTGcd eQGLYI UfGOjb GdESJKeGQ(B- (3CgOGa eQGLYI UfGOjb GdESJKeGQ(B- (3ELQGAGJ eQGLYI UfGOjb GdESJKeGQ(B-(3YQhV dEHQGR eTGcd eQGLYI UfGOjb GdESJKeGQ aj eUQ hGdMdhd GdebJQMI(B- (3eQGLYI GdGOhGJ GdeGdjI GdeTJbI(B- (3WHjYI GdCOhGJ GdeGdjI GdeTJbI(B- (3GdCgOGa GdefThOI ef eQGLYI YedjGJ GdeTJbGJ(B- (3EWGQ eaJhM deQGLYI YedjGJ GdeTJbGJs
Keywords: (3GdESJKeGQs; (3GdHhQUGJs; (3eQGLYI GdMSGHGJs